2004
DOI: 10.1038/sj.emboj.7600485
|View full text |Cite
|
Sign up to set email alerts
|

UvrD helicase, unlike Rep helicase, dismantles RecA nucleoprotein filaments in Escherichia coli

Abstract: The roles of UvrD and Rep DNA helicases of Escherichia coli are not yet fully understood. In particular, the reason for rep uvrD double mutant lethality remains obscure. We reported earlier that mutations in recF, recO or recR genes suppress the lethality of uvrD rep, and proposed that an essential activity common to UvrD and Rep is either to participate in the removal of toxic recombination intermediates or to favour the proper progression of replication. Here, we show that UvrD, but not Rep, directly prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
269
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(282 citation statements)
references
References 69 publications
11
269
1
1
Order By: Relevance
“…Current models suggest that UvrD removes RecA assembled on single-stranded DNA (ssDNA) at a blocked replication fork to allow replication fork reversal to occur (15). This is consistent with in vitro experiments that have shown UvrD to be capable of removing RecA molecules from DNA thereby disrupting a recombination event (9,18,18,19). It has also been suggested that UvrD could act to resolve the intermediate formed by replication fork regression so that the lesion may be repaired or bypassed immediately (16,20).…”
supporting
confidence: 61%
See 1 more Smart Citation
“…Current models suggest that UvrD removes RecA assembled on single-stranded DNA (ssDNA) at a blocked replication fork to allow replication fork reversal to occur (15). This is consistent with in vitro experiments that have shown UvrD to be capable of removing RecA molecules from DNA thereby disrupting a recombination event (9,18,18,19). It has also been suggested that UvrD could act to resolve the intermediate formed by replication fork regression so that the lesion may be repaired or bypassed immediately (16,20).…”
supporting
confidence: 61%
“…In addition, UvrD has been shown to unwind RNA-DNA hybrids (41) as well as displacing RecA bound to ssDNA (9,19). The promiscuous unwinding activity of UvrD is likely a reflection of its multiple roles in the cell including roles in repair, replication, and recombination consistent with the pleiotropic phenotype of uvrD mutants (1).…”
Section: Discussionmentioning
confidence: 93%
“…Pre-initiation complexes spontaneously isomerize under these conditions to yield an open complex, with the two DNA strands separated from approximately Ϫ3 to ϩ8, relative to the site of initiation (ϩ1), to form a transcription bubble. 6 The ability of the MCM helicase to unwind this DNA when bound into pre-initiation complexes (Fig. 4) was determined when the directions of helicase movement and transcription were the same (co-direction; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In temperature-sensitive dnaN and dnaE cells, UvrD has been implicated in the removal of RecA molecules that are bound to the arrested replication forks (13). Similarly, UvrD disrupts RecA bound to synthetic recombination intermediates, and it is hypothesized that in the absence of UvrD, the inability to disrupt RecA filaments leads to the hyper-recombinogenic phenotype (14). In agreement with these conclusions, cells expressing the hyper-helicase mutant of UvrD (UvrD303) have anti-recombinogenic and anti-mutator phenotypes (15,16).…”
mentioning
confidence: 99%